Upaya Mengatasi Rendahnya Minat Belajar Bahasa Inggris Melalui Pendekatan Teaching at the Right Level (TaRL) dan Media Interaktif di Kelas VII-8 SMP Negeri 2 Kisaran - Sinaga, Lista Kumalasari; Rahma Yunita Ansi; Endang Dorisday Sitorus (ELP (Journal of English Language Pedagogy), 2025)
This study addresses the low level of student interest in English learning among Grade VII-8 students at SMP Negeri 2 Kisaran by implementing the Teaching at the Right Level (TaRL) approach in combination with interactive media. The primary challenge identified was students’ lack of engagement, which contributed to reduced participation and suboptimal learning outcomes. Employing a Classroom Action Research (CAR) design over two cycles, the study followed the stages of planning, implementation, observation, and reflection. The participants consisted of 32 students, with data collected through observation, documentation, and learning outcome tests. Results demonstrated a positive impact on both student interest and academic performance. Notably, the proportion of students in the “very good” performance category (scores 90–100) increased from 0% to 6.6%, and those in the “good” category (80–89) rose from 6.6% to 26.7%. Concurrently, the number of students in the “poor” category (below 75) decreased from 55.7% to 41.4%. Observations also indicated improved classroom participation, enthusiasm, and involvement in discussions. While these findings suggest that the TaRL approach and interactive media can enhance student engagement and outcomes, further research employing statistical analysis is recommended to confirm the significance of these improvements.